Students’ Instrumental and Integrative Motivation in Learning English as A Foreign Language in Indonesia - Piping Rahadianto; Moh. Choirul Huda; Muhammad Al Hadaad (STKIP PGRI Trenggalek, 2022)
English as one of the most appealing subjects for student at University especially in Indonesia. Over the decade English is the subject that many students want to mastered it. To achieved it, student need to learn English as the way they need it for specific goals. One of the aspects to reach the goal in learning English is motivation. Motivation has been broadly accepted by both teachers and researchers as one of the most significant factors that influence and affect the rate and success of foreign language learning. Because teaching and learning English is not only the cognitive aspects on its but also there is psychology aspect how maintain the point of view in every student how to achieved new material as the language input that is very different with their native language. Inspired by such resume above, the study on which the present article is based aimed to investigate and to knowing kind of motivation such as instrumental and integrative motivation for student who learn English as a foreign language in Indonesia. A quantitative and qualitative analysis of the responses to a questionnaire of 50 students at university, it sought to examine the relative importance of motivational variables as theorised in the field of second language motivation. It also aimed to go further, by considering the kinds of motivation on its’. This study has gained pertinent insights on the information regarding the type and level of motivation that influence students the most. The discussions and the result is that majority of the students are integratively motivated. There is a need to motivate the students more integratively and also instrumentally.